Sticks and carrots for the design of international climate agreements with renegotiations - Hans-Peter Weikard; Rob B. Dellink (Fondazione Eni Enrico Mattei (FEEM), 2008)
This paper examines stability of international climate agreements for carbon abatement under an optimal transfer rule and renegotiations. The optimal transfer rule suggested to stabilise international environmental agreements (Weikard 2005, Carraro, Eyckmans and Finus 2006) is no longer optimal when agreements are renegotiated. We determine the conditions for optimal self-enforcing sequences of agreements. If these conditions are met, then transfer payments can be arranged such that no country wants to change its membership status at any stage. In order to demonstrate the applicability of our condition we use the STACO model, a 12-regions global model, to assess the impact of welldesigned transfer rules on the stability of an international climate agreement. Although there are strong free-rider incentives, we find a stable grand coalition in the first commitment period in a game with one round of renegotiations.
Keywords: C72; D62; H41; H77; 330; Stability of Coalitions; International Environmental Agreements; Partition Function Approach; Sharing Rules; Optimal Transfers; Renegotiations; Klimaschutz; Umweltabkommen; Internationale Umweltpolitik; Koalition; Internationaler Transfer; Theorie